2015
DOI: 10.1155/2015/946787
|View full text |Cite
|
Sign up to set email alerts
|

Trichomonas vaginalisCysteine Proteinases: Iron Response in Gene Expression and Proteolytic Activity

Abstract: We focus on the iron response of Trichomonas vaginalis to gene family products such as the cysteine proteinases (CPs) involved in virulence properties. In particular, we examined the effect of iron on the gene expression regulation and function of cathepsin L-like and asparaginyl endopeptidase-like CPs as virulence factors. We addressed some important aspects about CPs genomic organization and we offer possible explanations to the fact that only few members of this large gene family are expressed at the RNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 111 publications
(322 reference statements)
1
49
0
1
Order By: Relevance
“…Although some cysteine proteases are reportedly regulated at the posttranscriptional level by an iron-responsive element/iron response protein-like system56, iron-dependent gene regulation at the transcriptional level has been described only for the ap65 - 1 gene. The ap65 - 1 gene has an iron-inducible core promoter and several regulatory elements that are recognized by three Myb transcription factors, TvMyb1, TvMyb2, and TvMyb3303132333435.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some cysteine proteases are reportedly regulated at the posttranscriptional level by an iron-responsive element/iron response protein-like system56, iron-dependent gene regulation at the transcriptional level has been described only for the ap65 - 1 gene. The ap65 - 1 gene has an iron-inducible core promoter and several regulatory elements that are recognized by three Myb transcription factors, TvMyb1, TvMyb2, and TvMyb3303132333435.…”
Section: Discussionmentioning
confidence: 99%
“…The ap65 - 1 gene has an iron-inducible core promoter and several regulatory elements that are recognized by three Myb transcription factors, TvMyb1, TvMyb2, and TvMyb3303132333435. Although the presence of Myb recognition elements are shared by other genes, no direct evidence on the role of this regulatory element in iron-dependent gene transcription has been provided for other genes56. In the present study, we reported for the first time that histone modifications contribute to iron-dependent transcriptional regulation in T. vaginalis .…”
Section: Discussionmentioning
confidence: 99%
“…More recent quantitative proteomic analyses have identified surface membrane proteins that are released to the T. vaginalis environment upon cleavage by rhomboid protease (31). The best-studied group of secreted proteins is the proteases, including cysteine proteases and metalloproteases (17,32,33). Kucknoor et al (34) identified 32 various secreted proteins, including a putative adhesin, AP65, via 2-D SDS-PAGE followed by MALDI-TOF (34).…”
mentioning
confidence: 99%
“…T. vaginalis uses multiple sources of iron from the host cells such as lactoferrin (Lf), hemoglobin (Hb) and heme. It has multiples iron uptake systems mediated by specific receptors: receptor for binding the cytochrome C, a 136 kDa receptor for binding the host holo-Lf and even uses the adhesins AP65 and AP51 as heme- and hemoglobin-binding proteins [ 17 ]. This parasite also internalizes ferritin, but not transferrin.…”
Section: Introductionmentioning
confidence: 99%